Chilean EFL Teacher Trainees’ Beliefs Regarding the EFL Teacher Competences - Donoso, Eladio (2021)
There is abundant literature regarding second language (L2) or foreign language (FL) teachers’ beliefs. However, there exists very little literature on this matter that involves L2/FL teacher trainees. This study aims to find out Chilean EFL teacher trainees’ beliefs regarding the competences EFL teachers should have for their professional performance.  Three competence domains are under scrutiny: (1) English linguistic competence and English culture, (2) English teaching didactics, and (3) professional attitude. A Likert scale questionnaire was used to collect data from 208 EFL teacher trainees of four Chilean universities. These trainees are in their first (N=129) and fourth year (N=79) of an EFL teacher training program. General results show that the most important competence domain for the participants is the professional stance, especially for fourth year students.